Genetic and physiological autonomic nervous system factors involved in failed back surgery syndrome: A review of the literature and report of nine cases treated with pulsed radiofrequency - Baronio, Manuela; Baglivo, Mirko; Natalini, Giuseppe; Notaro, Paolo; Dautaj, Astrit; Paolacci, Stefano; Bertelli, Matteo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: failed back surgery syndrome is one of the most important causes of chronic low back pain that involve the physiology of autonomic nervous system factors. Some genetic and molecular factor can be determinant in the development of failed back surgery syndrome and novel therapy are needed. Pulsed radiofrequency treatment could be an innovative treatment option for this syndrome. Methods: 44 patients classified with failed back surgery syndrome from the Poliambulanza Foundation Hospital of Brescia patients were treated with standard therapy for six months; 9 of these patients who showed no improvement were candidates for pulsed radiofrequency therapy for three months. Results and Conclusions: reduction of lumbar and radicular pain, disability and number of drug classes prescribed improved significantly (p